Driverless Cars – Pro Et Contra - Tomić-Petrović, Nataša M.; Miladinović, Slobodan M. (Sociološki pregled, 2019)
This article discusses worldwide experiences in testing and acceptance of vehicles without drivers, highlights the importance of legal regulation of autonomous vehicles in particular through the analysis of legal regulation in the country that has achieved the most in the development of this technology and its present-day use, it provides a sociological dimension of the use of these vehicles, and then discusses the relationship of the Republic of Serbia towards the vehicles of the future and the advantages and disadvantages that they bring. Legal requirements are only one, but significant obstacle for the vehicles without drivers, though the circumstances in this area are gradually changing.